2010
DOI: 10.1155/2010/647198
|View full text |Cite
|
Sign up to set email alerts
|

A Dislocation-Based Theory for the Deformation Hardening Behavior of DP Steels: Impact of Martensite Content and Ferrite Grain Size

Abstract: A dislocation model, accurately describing the uniaxial plastic stress-strain behavior of dual phase (DP) steels, is proposed and the impact of martensite content and ferrite grain size in four commercially produced DP steels is analyzed. It is assumed that the plastic deformation process is localized to the ferrite. This is taken into account by introducing a nonhomogeneity parameter, f(ε), that specifies the volume fraction of ferrite taking active part in the plastic deformation process. It is found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 14 publications
7
29
0
Order By: Relevance
“…Ignoring the simplifications of this model, it can be observed that the slope of this curve is positive but with descending second derivative, just as the predicted evolutions by theoretical dislocation balance equations [18,19].…”
Section: Discussionmentioning
confidence: 51%
“…Ignoring the simplifications of this model, it can be observed that the slope of this curve is positive but with descending second derivative, just as the predicted evolutions by theoretical dislocation balance equations [18,19].…”
Section: Discussionmentioning
confidence: 51%
“…Speich & Miller 43 ascertained this statement in dual-phase steels. Also, the original Bergström dislocation theory 44 , but adjusted for dual-phase steels 45 , is employed in order to justify the plastic deformation process in these steels. However, according to this theory, the deformation is considered to be entirely supported by the ferrite phase, conversely to several authors 6,36 who consider plastic deformation in martensite.…”
Section: Ashbymentioning
confidence: 99%
“…Bergström et al (2010). A uniaxial tensile test usually forms the basis of the characterisation, either directly from experimental data or by an analytical expression fitted to this data.…”
Section: Plastic Strain Hardeningmentioning
confidence: 99%